2006
DOI: 10.1136/jcp.2005.031708
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of postmortem radiology to the diagnosis of fatal cerebral gas embolism from compressed air diving

Abstract: Aims : To test the hypothesis that artefact caused by postmortem off-gassing is at least partly responsible for the presence of gas within the vascular system and tissues of the cadaver following death associated with compressed air diving. Methods : Controlled experiment sacrificing sheep after a period of simulated diving in a hyperbaric chamber and carrying out sequential postmortem computed tomography (CT) on the cadavers. Results: All the subject sheep developed significant quantities of gas in the vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…In a second study, sheep were euthanatized after a period of simulated diving in a pressurized air; the cadavers were then examined by sequential postmortem CT at surface Vet Pathol 46:3, 2009 pressure. 7 All the sheep developed significant quantities of gas in the vascular system within 24 hours, as demonstrated by CT and necropsy, while the control animals did not. Those authors concluded that the presence of gas in the vascular system of human cadavers after diving-associated fatalities was to be expected and is not necessarily connected with gas embolism after pulmonary barotrauma, as had previously been claimed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a second study, sheep were euthanatized after a period of simulated diving in a pressurized air; the cadavers were then examined by sequential postmortem CT at surface Vet Pathol 46:3, 2009 pressure. 7 All the sheep developed significant quantities of gas in the vascular system within 24 hours, as demonstrated by CT and necropsy, while the control animals did not. Those authors concluded that the presence of gas in the vascular system of human cadavers after diving-associated fatalities was to be expected and is not necessarily connected with gas embolism after pulmonary barotrauma, as had previously been claimed.…”
Section: Discussionmentioning
confidence: 99%
“…In a controlled experiment using a sheep as a model, it was reported that small gas pockets could be imaged on CT within 24 hours postmortem with no dysbaric exposure. 7 The amount of gas, however, was minimal and would likely be overlooked in dissection. The failure of case No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21.41) as well as the lung, sinus and ear changes associated with barotrauma. These techniques are more accurate than plain radiography or conventional autopsy techniques and provide detailed information on the extent and distribution of gas in tissues that is inaccessible by standard autopsy or in tissues from which bubbles may vanish during autopsy procedures (Plattner et al 2003;Cole et al 2006). MRI can also detect DCS-associated spinal cord changes (Gempp et al 2008).…”
Section: Radiology Computed Tomography and Magnetic Resonance Imagingmentioning
confidence: 99%
“…3). This is a well-recognized phenomenon in clinical radiological practice whereby gas is introduced along the line of needle tracks and has been demonstrated on CT in an experimental sheep model [7]. There were also 1 or 2 small bubbles of IHG and no ICG ( Fig.…”
Section: External Examinationmentioning
confidence: 94%